Perlindungan Hukum Terhadap Debitur Dalam Penarikan Objek Jaminan Fidusia Secara Sepihak - Jimmy Petra Latumanuwy; Adonia Ivone Laturete; Syadzwina Hindun Nabila (PATTIMURA Law Study Review, 2026)
Protection of debtors regarding the withdrawal of fiduciary collateral objects cannot be carried out simply without proper legal processes, such as prior notification to the debtor and, if necessary, through the courts. Results: This study shows that the Procedure for Withdrawing Fiduciary Guarantee Objects is carried out by providing a warning letter to debtors who have experienced delays in installment payments, Legal Protection for Debtors in Withdrawing Fiduciary Guarantee Objects unilaterally should be regulated and in the credit agreement and it must be agreed that in the case of carrying out the execution of the fiduciary guarantee object, a decision letter must first be obtained from the court, so that when the creditor carries out the execution by force or unilaterally in this case if it is found that during the execution they have not obtained a decision letter from the court, the debtor may refuse or file a lawsuit with the court either civilly or criminally.